Phytochemical Composition and Cytoprotective Properties of the Endemic Sideritis sipylea Boiss Greek Species: A Valorization Study - Silvia Di Giacomo; Antonella Di Sotto; Apostolis Angelis; Ester Percaccio; Annabella Vitalone; Marco Gullì; Alberto Macone; Evangelos Axiotis; Alexios Leandros Skaltsounis (MDPI AG, 2022)
Sideritis sipylea Boiss. (Fam. Lamiaceae) is an endemic plant of the North Aegean Islands (Greece), commonly known as ironwort. Traditionally, its aerial parts have been used to relieve several ailments, especially gastrointestinal disorders, however, with scant knowledge about the pharmacological basis. In the present study, an endemic S. sipylea Greek species from Lesvos Island has been characterized for phytochemical composition and biological activities, in order to give a possible scientific basis to its traditional use and to highlight a further nutraceutical interest as a source of bioactive phytochemicals and extracts. Three different fractions obtained from a methanolic extract of S. sipylea aerial parts by using ethyl acetate with 10 (S10), 20 (S20), and 50% (S50) methanol as fractionation solvents were phytochemically characterized. Moreover, their antioxidant power and cytoprotective activity in different human cell lines were evaluated. The phytochemical analysis highlighted the presence of flavonoids, iridoids, and phenolic acids in all the tested samples. Particularly, the S10 fraction mainly contained iridoids, while S20 and S50 lavandulifolioside and chlorogenic acid, respectively. The fractions also showed antioxidant properties, S10 and S20 being the most potent. When assessed in human cholangiocytes, they counteracted the cytotoxicity of the tBOOH pro-oxidant agent, by reducing ROS levels and affecting GSH antioxidant system. The present findings highlight a possible interest in S10 and S20 fractions from S. sipylea as sources of bioactive molecules and stimulate further studies in order to characterize their possible application for nutraceutical and pharmaceutical purposes.